Implementation and Performance Analysis of Convolution Codeon WARP (Wireless Open Access Research Platform) - Kuswidiastuti, Devy; Suwadi, Suwadi; Suryani, Titiek; Elvia, Desrina (JAVA Journal of Electrical and Electronics Engineering, 2015)
In order to have a reliable and robust data transmission in digital communication system, channel coding is applied for improving the performance of the system. Convolutional code is one of channel coding technique for error detection and error correction. In this paper, convolutional code is used for improving the bit error rate (BER) performance in Quadrature Phase Shift Keying (QPSK)modulation scheme which is implemented on a Wireless Open-Access Research Platform (WARP). Based on implementation and measurement results show that with an equal transmit power (with Tx gain =20dB), QPSK modulation with convolutional code have a lower BER than the uncoded one. For convolutional code with rate =1/2 at a range of 6 meter has a BER value of 0.00065232 while the uncoded BER is 0.0048828. By comparison of the system performance with different coding rate (1/2,2/3,3/4.5/6 and 7/8), the BER performance of QPSK system with convolutional code rate of 7/8 is better that the others. It can achieve a BER of 0.00037495.